Perspectives on the Intersection of Multiculturalism and Positive Psychology - Teramoto Pedrotti, Jennifer; Edwards, Lisa M.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2014)
This book provides the first comprehensive collection of topics that lie within the intersection of positive psychology and multicultural issues. Written by leaders in the field and using a broad definition of culture (including race, ethnicity, socioeconomic or social class status, disability status, religion/spirituality, sexual orientation, and gender), this book reviews relevant research, theory, and suggestions for practice and highlights the importance of considering context within a strengths-based framework. Beginning with a history of the intersection of multiculturalism and positive psychology and issues related to measurement and methodology, the volume proceeds to specific examples of current research in multiple areas of cultural identity. Finally, domains (e.g., school, work, psychotherapy) in which the findings of this work can be applied are described, as are directions for future theory and research in this area. This volume is aimed at students, scholars, and practitioners across several fields including multicultural psychology, positive psychology, counseling and clinical psychology, school psychology, social psychology, as well as marriage and family counseling, and social work. It will serve as an important reference to any who are interested in learning about the intersection of positive psychology and multiculturalism.
Foreword; Shane J. Lopez -- Preface; Jennifer Teramoto Pedrotti and Lisa Edwards -- Part I. Theoretical Underpinnings and Research Issues -- Chapter 1. History of Cultural Context in Positive Psychology: We Finally Come to the Start of the Journey; Christina Downey and Edward C. Chang -- Chapter 2. Broad Definitions of Culture in the Field of Positive Psychology; Heather N. Rasmussen and Lea Lavish -- Chapter 3. Multicultural Considerations in Measurement and Classifications of Positive Psychology; Cristalis Capielo, Lauren Mann, Baileu Nevels and Edward Delgado-Romero -- Chapter 4. Methodological Issues in Positive Psychology Research with Diverse Populations: Exploring Strengths among Chinese Adults; Samuel M.Y. Ho, Tina L. Rochelle, Lawrence S.C. Law, Wenjie Duan, Yu Bai and Shih-Ming Shih -- Part II. Specific Constructs -- Chapter 5. Affective Well-Being Viewed through a Lens of Race and Ethnicity; Hung-Bin Sheu -- Chapter 6. Cognitive Constructs in the Context of Positive Psychology; Christine Robitshek, Danielle Sirles and Erin E. Hardin -- Chapter 7. Relationships in Multicultural Contexts; Belinda Campos and Sharon Shenhav -- Part III. Specific Populations -- Chapter 8. Positive Psychology across the Lifespan; Jeanne Nakamura, Michael Waren, Brittany Branand, Pi-Ju Liu, Brett Wheeler and Thomas Chan -- Chapter 9. Positive Psychology and Gender; Matt Englar-Carlson and Rebekah Smart -- Chapter 10 Religion, Spirituality and Positive Psychology: Strengthening Well-Being; Melissa D. Falb and Kenneth I. Pargament -- Chapter 11. Social Class Mobility and Positive Psychology; Michael L. Weymeyer and Karrie A. Shogren -- Chapter 13. Positive Psychology and LGBTQ Populations; Sharo G. Horne, Julia A. Puckett, Raphael Apter and Heidi M. Levitt -- Part IV. Applications of Positive Psychology in Multicultural Contexts -- Chapter 14. Positive Psychological Practices in Multicultural School Settings; Casey A. Holtz and Michael J. Martinez -- Chapter 15. A Positive Approach to Multiculturalism and Diversity Management in the Workplace; Carolyn M. Youssef-Morgan and James Hardy -- Chapter 16. Infusing Multiculturalism and Positive Psychology in Psychotherapy; Jeana L. Magyar-Moe -- Part V. Conclusion -- Chapter 17. Future Directions for a More Multiculturally Competent (and Humble) Positive Psychology; John Chambers Christopher and Katie Howe.
Keywords: Psychology; Medical research; Quality of life; Positive psychology; Psychology; Positive Psychology; Quality of Life Research; Electronic books